OPTIMASI KONDISI EKTRAKSI VANILLIN HASIL DEGRADASI LIGNOSELULOSA BAGAS TEBU MENGGUNAKAN RESPONSE SURFACE METHOD (RSM) - Irnia Nurika; Faudina Nurin Nisa'; Nurul Azizah; Sri Suhartini (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2021)
Optimization of Vanillin Extraction Conditions from Lignocellulose Degradation of Sugarcane Bagasse using the Response Surface Method (RSM) Sugarcane bagasse is an agricultural waste containing lignocellulose and has the potential to be processed into high-value chemicals such as vanillin. The degradation of sugarcane bagasse lignocellulose can be carried out biologically by the white rot fungus Phanerochaete chrysosporium. This study aims to obtain optimal extraction conditions in the form of ethyl acetate solvent volume and extraction time, using the response surface method (RSM). Two optimized factors were the volume of ethyl acetate (71.72; 80; 100; 120; and 128.28 mL) and the extraction time (35.16; 60; 120; 180; 204.84 minutes). The response variables were the concentration (%) and yield of vanillin (µg g–1). The research on the optimization of the response of vanillin levels and vanillin yield was carried out at 14 days incubation with the highest average total soluble phenol (TSP) value of 0.101 mg g–1. The optimal condition of ethyl acetate volume of 109.730 mL with an extraction time of 137.302 minutes was predicted to produce vanillin levels and yields of 0.0078% and 8.9089 g g–1, respectively, with an accuracy value of 93.4%. Based on the verification results, the optimal vanillin concentration and yield were 0.0077% and 8.9805 g g–1, respectively. Bagas tebu merupakan limbah pertanian yang mengandung lignoselulosa dan berpotensi diolah menjadi bahan kimia bernilai tinggi seperti vanillin. Degradasi lignoselulosa bagas tebu dapat dilakukan secara biologis oleh jamur pelapuk putih Phanerochaete chrysosporium. Penelitian ini bertujuan mendapatkan kondisi ekstraksi optimal berupa volume pelarut etil asetat dan lama waktu ekstraksi, menggunakan response surface method (RSM). Dua faktor yang dioptimasi adalah volume etil asetat (71,72; 80; 100; 120; dan 128,28 mL) dan lama waktu ekstraksi (35,16; 60; 120; 180; 204,84 menit). Variabel respons adalah kadar (%) dan yield vanillin (µg g–1). Penelitian optimasi respons kadar vanillin dan yield vanillin dilakukan pada inkubasi 14 hari dengan nilai total soluble phenol (TSP) rata-rata tertinggi 0,101 mg g–1. Kondisi optimal volume etil asetat 109,730 mL dengan waktu ekstraksi 137,302 menit diprediksi menghasilkan kadar dan yield vanillin sebesar 0,0078% dan 8,9089 µg g–1 dengan nilai ketepatan 93,4%. Berdasar hasil verifikasi, konsentrasi dan yield vanillin yang optimal masing-masing adalah 0,0077% dan 8,9805 µg g–1.